2017
DOI: 10.1016/j.mce.2017.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Function of the vitamin D endocrine system in mammary gland and breast cancer

Abstract: The nuclear receptor for 1α,25-dihydroxycholecalciferol (1,25D), the active form of vitamin D, has anti-tumor actions in many tissues. The vitamin D receptor (VDR) is expressed in normal mammary gland and in many human breast cancers suggesting it may represent an important tumor suppressor gene in this tissue. When activated by 1,25D, VDR modulates multiple cellular pathways including those related to energy metabolism, terminal differentiation and inflammation. There is compelling pre-clinical evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 79 publications
1
69
0
3
Order By: Relevance
“…These facts suggest that the highest VDR expression occurs in well‐differentiated cells and its expression decreases in poorly differentiated cells. In human breast cancer, several authors have showed that VDR protein expression declines in highly aggressive tumours . Furthermore, the well‐differentiated ME cells appear to be the canine mammary cell type that exhibits greater VDR expression, pointing to the presence of ME cells with different phenotypic characteristics in malignant tumours as formerly reported in the canine and human species …”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…These facts suggest that the highest VDR expression occurs in well‐differentiated cells and its expression decreases in poorly differentiated cells. In human breast cancer, several authors have showed that VDR protein expression declines in highly aggressive tumours . Furthermore, the well‐differentiated ME cells appear to be the canine mammary cell type that exhibits greater VDR expression, pointing to the presence of ME cells with different phenotypic characteristics in malignant tumours as formerly reported in the canine and human species …”
Section: Discussionmentioning
confidence: 66%
“…This result suggests that VDR could represent an important tumour suppressor protein. In humans, several authors have demonstrated that the VDR protein is expressed in samples from normal breast tissues and also in breast cancer biopsy specimens, but detailed insight into its distribution, regulation and function are still emerging . There is discrepancy both in whether the VDR expression is greater in normal or tumour breast tissue, as in the percentage of carcinomas expressing VDR protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a tumor biology point of view, removal of the tumor by surgical resection and chemotherapy may have also resulted in recovery of circulating 25(OH)D 3 levels. Previous studies suggested that regulation of the vitamin D pathway may be altered in breast cancer cells (39,40). For example, more stable CYP24 mRNA profiles, responsible for clearing of the active metabolite 1,25(OH) 2 D, were found in human breast cancer cells as compared to normal human mammary epithelial cells (41).…”
Section: Discussionmentioning
confidence: 98%